Superhydrophilicity to superhydrophobicity transition of CuO nanowire films - Chang, Feng-Ming; Cheng, Shao-Liang; Hong, Siang-Jie; Sheng, Yu-Jane; Tsao, Heng-Kwong (Applied physics letters, 2010)
The surface of CuO is known for its hydrophilicity and exhibits superhydrophilic nature as nanowires are present. When exposed in the air at room temperature or treated by low temperature annealing, however, transition from superhydrophilicity to superhydrophobicity of the CuO nanowire films are observed. Since the chemical structure of the films after treatment remains the same as CuO according to x-ray photoelectron spectroscopy spectra, the superhydrophobicity may be attributed to partial deoxidation of the upmost layer of CuO surfaces into Cu2O-like hydrophobic surfaces. Nonetheless, superhydrophilicity is recovered if the superhydrophobic CuO film is subject to high temperature annealing.